Cutaneous Mycobacterium chelonae in a Patient with Sjogren’s Syndrome - Guo L (Dove Medical Press, 2021)
Lu Guo,1 Sha Lv,1 Jing Zeng,1 Jiayu Yang,2 Baihui Shan,1 Fuqiu Li1 1Department of Dermatology, The Second Hospital of Jilin University, Changchun, Jilin, People’s Republic of China; 2Department of Obstetrics and Gynecology, China-Japan Union Hospital of Jilin University, Changchun, Jilin, People’s Republic of ChinaCorrespondence: Fuqiu Li Tel +8613039123758Fax +86-431-81136888Email lifuqiu1234@126.comAbstract: A case of cutaneous Mycobacterium chelonae infection in a patient with Sjogren’s syndrome (SS) was misdiagnosed as sporotrichosis. A 56-year-old female patient was admitted to another hospital. Based on results of the histopathological examination and secretion culture obtained at the other hospital, the patient was diagnosed with sporotrichosis and received antifungal therapy. After treatment failure, the patient was admitted to our hospital, and a histopathological examination and secretion culture were performed again. The secretion culture revealed the presence of Mycobacterium chelonae. The antinuclear antibody test suggested SS, and the patient was treated with antibiotics and corticosteroids.Keywords: Mycobacterium chelonae, cutaneous infection